SEC Rule 10b5-1 and Insiders' Strategic Trade - Jagolinzer, Alan D. (Management Science, 2009)
The U.S. Securities and Exchange Commission enacted Rule 10b5-1 to deter insiders from trading with private information, yet also protect insiders' preplanned, non-information-based trades from litigation. Despite its requirement that insiders plan trades when not privately informed, the rule appears to enable strategic trade. Participating insiders' sales systematically follow positive and precede negative firm performance, generating abnormal forward-looking returns larger than those earned by nonparticipating colleagues. The observed association does not appear to be explained by market transaction disclosure response, “predictable” reversion following positive performance, or general periodic price declines. There is evidence, however, that a substantive proportion of randomly drawn plan initiations are associated with pending adverse news disclosures. There is also evidence that early sales plan terminations are associated with pending positive performance shifts, reducing the likelihood that insiders' sales execute at low prices. Collectively, this suggests that, on average, trading within the rule does not solely reflect uninformed diversification.